If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(5y + -5) + -1y = -3(y + -2) Reorder the terms: -5(-5 + 5y) + -1y = -3(y + -2) (-5 * -5 + 5y * -5) + -1y = -3(y + -2) (25 + -25y) + -1y = -3(y + -2) Combine like terms: -25y + -1y = -26y 25 + -26y = -3(y + -2) Reorder the terms: 25 + -26y = -3(-2 + y) 25 + -26y = (-2 * -3 + y * -3) 25 + -26y = (6 + -3y) Solving 25 + -26y = 6 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 25 + -26y + 3y = 6 + -3y + 3y Combine like terms: -26y + 3y = -23y 25 + -23y = 6 + -3y + 3y Combine like terms: -3y + 3y = 0 25 + -23y = 6 + 0 25 + -23y = 6 Add '-25' to each side of the equation. 25 + -25 + -23y = 6 + -25 Combine like terms: 25 + -25 = 0 0 + -23y = 6 + -25 -23y = 6 + -25 Combine like terms: 6 + -25 = -19 -23y = -19 Divide each side by '-23'. y = 0.8260869565 Simplifying y = 0.8260869565
| 2z^3-5=0 | | 3(x-30)=12x | | 1=y/9-1 | | .6(4x+8)=1.1-(x+2) | | (4+2)(3+6)= | | y=5.8x | | 20x+12y=32 | | a+18=5a-3+2 | | (4z+4)(2z^2+3z+1)= | | 14v^2+8v+32=0 | | 4x^2=9x-5 | | 4x+16=8x+12 | | y/2-2=-2 | | -2x-3.8=-31.3+3x | | 12x-15=7x+10 | | 6+12x=0 | | 3-9Y+8= | | 8.7x-4.5/7.22 | | -4z-5.1=-29.6+3z | | 8=z/10-10 | | m/5-46/5-m/4 | | .12x-.05y=2390 | | .9(7x+14)=1.7-(x+2) | | Log(x-7)=3 | | 2t^2-3t+2=equation | | a-3/8=-3/4 | | 24+10x-(x)(x)=p-(x-5)(x-5) | | 3x+2.7=-6.7+5x | | w/4=-14 | | -5u+2(u+5)=34 | | a+(-4)=-64 | | 3m+4n+5m+9n= |